2020
DOI: 10.1002/pmic.202000003
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Characterization of the Pseudomonas sp. Strain phDV1 Response to Monocyclic Aromatic Compounds

Abstract: The degradation of aromatic compounds comprises an important step in the removal of pollutants and re‐utilization of plastics and other non‐biological polymers. Here, Pseudomonas sp. strain phDV1, a gram‐negative bacterium that is selected for its ability to degrade aromatic compounds is studied. In order to understand how the aromatic compounds and their degradation products are reintroduced in the metabolism of the bacteria and the systematic/metabolic response of the bacterium to the new carbon source, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 43 publications
0
17
0
Order By: Relevance
“…Mass spectrometry-based proteomics has been used to understand the aromatic biodegradation pathways in Pseudomonas sp. strain phDV1 [ 10 , 11 , 13 , 14 , 15 ]. These studies have shown that Pseudomonas sp.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mass spectrometry-based proteomics has been used to understand the aromatic biodegradation pathways in Pseudomonas sp. strain phDV1 [ 10 , 11 , 13 , 14 , 15 ]. These studies have shown that Pseudomonas sp.…”
Section: Introductionmentioning
confidence: 99%
“…These studies have shown that Pseudomonas sp. strain phDV1 can metabolize 2.2 mM phenol and 1.9 mM cresols, respectively, via the meta -cleavage pathway [ 10 , 13 , 15 ]. Recent studies show that monocyclic aromatic substrates influence the central carbon metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…LY1. Lyratzakis et al, 2021). As shown in Figure 5, IAA-up DAPs were mainly grouped into three biological processes: IAA degradation, stress response, and membrane-related processes, and the three biological processes have interactions with each other.…”
Section: Discussionmentioning
confidence: 99%
“…Proteomic analysis is a useful tool to elucidate the global protein response to pollutant degradation ( Armengaud, 2016 ; Lyratzakis et al, 2021 ). As shown in Figure 5 , IAA-up DAPs were mainly grouped into three biological processes: IAA degradation, stress response, and membrane-related processes, and the three biological processes have interactions with each other.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation